An international perspective on young stroke incidence and risk factors: a scoping review - Dinah Amoah; Matthew Schmidt; Carey Mather; Sarah Prior; Manoja P. Herath; Marie-Louise Bird (BMC, 2024)
Abstract Background Stroke among younger age groups is increasing globally. While there is a focus on research conducted on people under 65 years who have had a stroke, there is a paucity of data on the incidence and risk factors of stroke among younger people (≤ 30 years). This scoping review examines evidence on incidence and risk factors for perinatal, paediatric and young adult stroke globally. Methods The review was guided by the Joanna Briggs Institute's scoping review methodology. A systematic search was conducted on 23rd March 2022 across Medline Ovid, Embase, PsycINFO and Cumulative Index to Nursing and Allied Health Literature (CINAHL). The eligibility criteria included all study designs providing information on the incidence and risk factors of stroke among young people (≤ 30 years) in the last ten years. Results A total of 5750 articles were identified. After screening, 471 articles (224 cohort studies (47.6%), 164 case studies/case series (34.8%), 35 reviews (7.4%), 30 case-control (6.4%) and 18 combinations of designs (3.8%) were included. There was data from 50 different countries, 199 studies were from high-income countries, upper and middle income (n = 38), lower middle-income (n = 39), low-income (n = 3) countries, international study (n = 7) and a further 185 articles did not state the country of research. Most of the studies (63%) focused on risk factors while incidence constituted 37%. Incidence data were reported heterogeneously across studies, leading to an inability to synthesise data. The three most frequently reported risk factors for perinatal stroke were infections, cardiac conditions, and intrapartum factors. Vasculopathies, infection and cardiac conditions accounted for most reported risk factors for paediatric stroke, while chronic conditions such as diabetes mellitus, vasculopathies and cardiac conditions accounted for the most reported risk factors among young adults. Conclusion This review has highlighted different stroke risk factors for each age cohort of people under 30 years. The low number of epidemiological studies suggests that further research of this type is needed to fully understand the incidence and risk factors in young stroke. A standardised reporting of age groupings of incidence data is imperative to enable the comparison of data from different geographical locations.